Kinerja Anggaran dan Kepuasan Satker Berbasis IKPA di KPPN Surakarta - Syifa Fatikasari; Agus Puji Priyono (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
This study aims to analyze budget implementation performance and work unit satisfaction based on the achievement of Budget Implementation Performance Indicators (IKPA) at KPPN Surakarta in 2024. The IKPA achievement of KPPN Surakarta in 2024 was recorded at 97.16, which fell into the “Very Good” category. This study also explores how KPPN's service quality affects Satker satisfaction, using the SERVQUAL service quality theory which includes the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. The research method used is qualitative with interviews, observation, and documentation. The results showed that although IKPA achievements were quite good, there were challenges in DIPA revisions, budget deviations, and late bills. The quality of KPPN services affects Satker satisfaction, which is also influenced by better coordination and budget management. This study recommends improving coordination and human resource capacity in Satker to overcome the challenges.